APPLICATION OF ANALYTIC HIERARCHY PROCESS IN SITE SELECTION OF URBAN CONSOLIDATION CENTERS - Vass, Lívia; Bányai, Tamás (Journal of Applied Engineering Science, 2026)
The Analytic Hierarchy Process (AHP) is a structured and widely-used multi-criteria decision-making (MCDM) method. This study applies AHP to evaluate and rank five potential sites for establishing an Urban Consolidation Center (UCC). UCCs serve as logistics hubs that aggregate deliveries in urban areas, aiming to reduce traffic congestion, emissions, and inefficiencies. The evaluation framework was developed using seven main criteria categories, each containing detailed sub-criteria. A hierarchy was constructed, and pairwise comparisons were conducted to derive weights. The consistency of judgments was verified using the Consistency Ratio (CR). The results yielded a final ranking of the locations, offering a rational and transparent approach to support urban logistics planning.